Effects of Rumours on IPO Success: A Qualitative Approach - Tomas Meluzin; Marek Zinecker; Karel Doubravský; Mirko Dohnal (Institute of Economic Research (IER), 2017)
In epidemiology, qualitative models have been developed and applied to study the propagation of infectious diseases since the 1920s. A version of these models is based on the rumour propagation. The main idea behind these models is that spreading an infectious disease or disseminating information are analogous phenomena. Recently, this idea has been used in several areas to analyse how a rumour affects the financial industry. The success of going public depends on many aspects including the predictability and visibility of the initial public offering candidate, enormous growth potential and no signals of a failure. However, the wide public of investors might be reached by rumours affecting significantly the success of initial public offerings. This paper examines the impact of rumours on success or failure of initial public offerings. Rumours might significantly affect the decision-making of uninformed investors while considering investments in newly issued shares and thus are an important phenomenon within going public procedures. The ISS (Ignorant-Spreader-Stifler) model is applied to study the impact of rumours on initial public offering success or failure. We assume that the information asymmetry is one of the most important reasons for spreading rumours. A case study experiment is conducted in order to validate the model. Our analysis of spreading rumours suggests that if there is a qualitative model consisting of a set of scenarios and a transitional graph, the decision makers may predict the development of ignorants (I), spreaders (S) and stiflers (R) in time. In such a case, no variant is overlooked, i.e. the model covers all possible changes of the situation in time. Supposing that rumours are under control of the issuing company, i.e. if detected in a timely manner and effective actions are introduced by decision makers, any reputational damages and thus initial public offering failure can be averted.
Keywords: G11; G12; G14; G23; 330; initial public offering; IPO; rumours; qualitative models; rumour spreading approach